Proposed mechanisms of action of herbal drugs and their biologically active constituents in the treatment of coughs: an overview - Pourova, Jana; Dias, Patricia; Pour, Milan; Bittner Fialová, Silvia; Czigle, Szilvia; Nagy, Milan; Tóth, Jaroslav; Balázs, Viktória Lilla; Horváth, Adrienn; Csikós, Eszter; Farkas, Ágnes; Horváth, Györgyi; et al. (PeerJ, 2023)
Various medicinal plants find their use in cough treatment, based on traditions and long-term experience. Pharmacological principles of their action, however, are much less known. Herbal drugs usually contain a mixture of potentially active compounds, which can manifest diverse effects. Expectorant or antitussive effects, which can be accompanied by others, such as anti-inflammatory or antibacterial, are probably the most important in the treatment of coughs. The aim of this review is to summarize the current state of knowledge of the effects of medicinal plants or their constituents on cough, based on reliable pharmacological studies. First, a comprehensive description of each effect is provided in order to explain the possible mechanism of action in detail. Next, the results related to individual plants and substances are summarized and critically discussed based on pharmacological in vivo and in vitro investigation.
Keywords: Medicinal plants; antitusika; Plant Extracts; Antiviral; Plants, Medicinal; Mechanism of action; Herbal drugs; lidé; Cough; Expectorant; expektorancia; Expectorants; Anti-inflammatory; kašel; Humans; fytoterapie; Antitussive Agents; Antibacterial; Antitussive; Phytotherapy; rostlinné extrakty; léčivé rostliny